Effect of Eu2O3 Concentrations Doped Li-Na-K Borate Glasses on Luminescence Properties for Red Emission Material - Jarucha, N.; Ruangtaweep, Y.; Meejitpaisan, P.; Nawarat, P.; Kanthang, P.; Wongdamnern, N.; Limsuwan, P.; Kim, H. J.; Kaewkhao, J.; Sareein, T. (My University, 2023)
This paper investigated the europium-doped lithium sodium potassium borate glasses (LNKBEu). Glass was made using a melt-quenching technique with a range of europium doping concentrations ranging from 0.0 to 5.0 mol%. The absorption spectra showed that photons in the visible light and near infrared ranges were absorbed by the LNKBEu glasses. Photon absorption at 394 nm can excite the mirror to emit a number of photons in the VIS region, such as 590, 613, 652, and 701 nm. The results showed that 3.0 mol% was the optimal concentration of LNKBEu glass. Therefore, 3.0LNKBEu glass was studied using Judd-Ofelt (JO) analysis, which revealed an interesting possibility of its use. This glass is a high power red laser device.
Keywords: Alkali borate glasses; europium; photoluminescence; rare earth